2020
DOI: 10.9734/ijecc/2020/v10i330183
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Yield, Seed and Seedling Quality Parameters of Rapeseed-mustard Varieties under Different Seed Priming Options

Abstract: Rationale: Crop production and quality of produce get affected by drought, stand establishment and low availability of nutrients. Apart from various prevailing methods, seed treatment through priming now-a-days has been found to noticeably improve crop establishment for increasing seed yield and quality. Aim: To study the effect of various seed priming options on rapeseed-mustard varieties. Place of Study: A field experiment was conducted at AB Block Farm, Bidhan Chandra Krishi Viswavidyalaya, Kaly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…Between the two varieties variety Maya (V 2 ) was found to be significantly superior in test weight and oil content except seed viability % this may be because of the freshly harvested seed lot have highest seed quality which may not show significant difference however, maximum test weight (3.91g), oil content (38.38%), seed viability (93.79%) was recorded in V 2 over V 1 . There findings were in accordance with the findings of (Rai et al 2017) who found that performance of mustard varieties in differ each other for seed viability, similar findings were reported by (Das et al, 2020).…”
Section: Resultssupporting
confidence: 92%
“…Between the two varieties variety Maya (V 2 ) was found to be significantly superior in test weight and oil content except seed viability % this may be because of the freshly harvested seed lot have highest seed quality which may not show significant difference however, maximum test weight (3.91g), oil content (38.38%), seed viability (93.79%) was recorded in V 2 over V 1 . There findings were in accordance with the findings of (Rai et al 2017) who found that performance of mustard varieties in differ each other for seed viability, similar findings were reported by (Das et al, 2020).…”
Section: Resultssupporting
confidence: 92%
“…These findings differed from Hussaini (1984) [10] in maize & from Singh, (2012) [15] in okra. These variation among varieties are may be due to genetic makeup of varieties or due to the accumulation of food reserves in seeds (Rai et al, 2017) [14] reported that performance of varieties in respect to seed viability, germination %, seedling length, seedling dry weight and seedling vigour index I & II were differ each other similar findings were reported by (Das et al, 2020) [7] .…”
Section: Resultssupporting
confidence: 54%
“…The imperative need for nutritionally rich edible oils is constantly increasing in our daily life due to expanding human population. India ranks fourth largest oilseed producing economy worldwide [2]. Among various oilseed crops in India and the rest of the globe, rapeseed-mustard (Brassica spp.)…”
Section: Introductionmentioning
confidence: 99%